PRICES, INFLATION, AND SMOKING ONSET: THE CASE OF ARGENTINA. (16th August 2017) - Guindon, G. Emmanuel; Paraje, Guillermo R.; Chávez, Ricardo
Abstract : This article examines the effect of tobacco prices on the decision to start smoking in Argentina. Argentina is an interesting case to explore given its high smoking rates, its recent experience with periods of very high and hyperinflation, and the mixed evidence of the effect of prices on smoking onset, particularly in low‐ and middle‐income countries. We used data from four cycles of two large national surveys conducted between 2005 and 2011 and discrete‐time hazard models. We found that tobacco prices had a statistically significant and fairly large impact on the hazard of smoking onset, and these findings were robust to alternative specifications. We also found that prices had little effect on the hazards of smoking onset during periods of hyper‐ and very high inflation, which provide some support for the notion that prices lose their informational role in such periods. Governments need to be cognizant that their most important policy tool to reduce tobacco use—taxes that increase real tobacco prices—is likely no longer effective during these times. ( JEL C41, H20, I12, I18)